COMMUNITY-BASED ASSESSMENT OF MENTAL HEALTH LITERACY AND WELL-BEING AMONG OLDER ADULTS IN SEMI- URBAN KARNATAKA: A CROSS-SECTIONAL STUDY - Mr. Mallikarjun Neperi; Dr. Pallawee Sheoran (The Bioscan, 2025)
ackground: Population ageing is accelerating globally, with India witnessing a rapid increase in its elderly population. Mental health problems among older adults often remain under-recognized due to stigma, limited awareness, and inadequate integration of mental health services into primary care. Mental health literacy plays a vital role in early identification, help-seeking behavior, and improved quality of life.